Financing Urban Rail Projects through Land Value Capture – The Indian Case - Sharma, Rohit (Curtin University, 2018)
The thesis has demonstrated that Indian cities and other emerging cities can implement economically and financially viable urban rail projects through tapping the land based financing. An integrated approach to transit, finance and urban land development, with private sector involvement from the concept stage, will create opportunities for higher economic value and partnerships. The thesis shows that the demand for electric urban rail will continue to grow due to policies on climate change.